TREATMENT OF SOYBEAN SEEDS WITH NITRAGIN DURING SECONDARY SOWING AND THE INFLUENCE OF MINERAL FERTILIZER APPLICATION RATES ON THE NUMBER OF ROOT TUBERS OF THE PLANT - Холдарова Дилпуза Эргашбоевна; Усмонова Гули Бахтиёржон қизи; Азимжонова Мохигул Эркинжон қизи (Web of Journals Publishing, 2024)
The article provides information on the number of tubers formed at the root of a plant when mineral fertilizers are applied at different rates when treating Orzu soybean seeds with nitragin, grown as a secondary crop.
Keywords: Reseeding, soybeans, nitragin, inoculation, mineral fertilizers, nitrogen, phosphorus, potassium, tubers.